2020
DOI: 10.1002/1878-0261.12755
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of smoking cessation on survival in cancer patients by integrative analysis of multi‐omics data

Abstract: Few studies have examined the association between smoking status (including former smokers) at diagnosis and overall survival among cancer patients. We aimed to assess the benefits of quitting smoking on cancer prognosis in cohorts of cancer patient smokers obtained from the Cancer Genome Atlas (TCGA) database. Hazard ratios (HR) were calculated to evaluate smoking behavior at cancer diagnosis (reformed smokers vs. current smokers) in association with overall survival using multivariate‐adjusted Cox regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…By plotting K-M curves, we found that current smokers had a worse prognosis than reformed smokers in most SCC cohorts, which was consistent with other studies (Li et al, 2020;Yang et al, 2020). Then, we found smoking-related genes and performed function analysis in LUSC, pointing out that HR was an important pathway of smoking to aggravate cancer.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…By plotting K-M curves, we found that current smokers had a worse prognosis than reformed smokers in most SCC cohorts, which was consistent with other studies (Li et al, 2020;Yang et al, 2020). Then, we found smoking-related genes and performed function analysis in LUSC, pointing out that HR was an important pathway of smoking to aggravate cancer.…”
Section: Discussionsupporting
confidence: 89%
“…To better predict the prognosis of each patient, we constructed a nomogram integrating risk scores, smoking status, and clinical information. As a practical tool to improve predictive accuracy, these methods have been applied in many studies on different cancers (Sun et al, 2020;Yang et al, 2020). The nomogram with different aspects of markers, including risk scores, smoking status, age, gender, and tumor stage, had high clinical application value, which might be a promising way to change clinical management (Birkhahn et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between modifiable lifestyles and the risk of neoplastic and chronic diseases of the genitourinary system has attracted researchers' attention for a long time (34)(35)(36)(37). And lifestyle interventions were found to improve clinical outcomes for cancer or chronic medical conditions, either directly or indirectly (34,(38)(39)(40). The bidirectional relationship between lifestyle factors and disease might be systemic and multifaceted, for which lifestyle interventions might have a positive impact on overall health in addition to optimizing the disease-specific outcomes (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, quitting smoking at diagnosis was recently shown to decrease the risk of death in cancer patients [73], and quitting smoking was suggested to alleviate its impact in patients with pneumonia and other COVID-19 associated infections [66,68,74], thus a beneficial advice to quit smoking together with another to lose overweight and to control the blood glucose levels might also help to lower the chances of SARS CoV-2 adenovirus and RNA-based vaccine potential autoimmunity in those individuals.…”
Section: The Potentially Higher-risk Groups and Potential Amelioration Of The Risksmentioning
confidence: 99%